Impact of conservation partnership on improving community welfare in the Gunung Masigit Kareumbi Hunting Park, West Java, Indonesia - Aris Munandar; Dolly Priatna; Rita Retnowati (Universitas Pakuan, 2022)
In conservation areas throughout Indonesia, there are at least 1.8 million hectares of open land in the form of damaged or degraded ecosystems following encroachment on conservation areas by local communities. Addressing this, the government of Indonesia has introduced a conservation partnership policy issued in 2018, namely the Director General of KSDAE Regulation No. P.6/KSDAE/SET/Kum.1/6/2018 concerning Technical Guidelines for Conservation Partnerships in Nature Reserves and Nature Conservation Areas. The objective of this study was to identify and analyze the impact of conservation partnerships on improving the welfare of the community in the Gunung Masigit Kareumbi Hunting Park (GMKHP). The research was conducted within the GMKHP area, with the samples taken from the community of Forest Farmer Groups (KTH) in the villages of Pelita Asih, Jaya Mekar, Sunda Mekar, Cikadu, Sukajaya, and Kaduwulung. The approach used in this study is qualitative. Data were collected by questionnaire survey, interviews, observations, and documentation in the field. Based on the results of the study, it is known that the production of pine resin tapping carried out by KTH members is as much as 29,033 kg/month or an average of 323 kg/person per month. This activity has an impact on increasing the income of KTH members by 170%, i.e. from their initial average income of Rp. 853,778 per month to become Rp. 2,307,278/month for each member. Additionally, there are also contributing funds to the neighborhood and social welfare coordinated by cooperatives, such as assistance for the poor and orphans, village treasury income, BUMDes (Village Enterprise) capital, wages for reading Qoran teachers, mosque maintenance, etc.